Continuous surface EMG power reflects the metabolic cost of shivering during targeted temperature management after cardiac arrest. (October 2018) - May, Teresa L.; Riker, Richard R.; Gagnon, David J.; Duarte, Christine; McCrum, Barbara; Hoover, Clifford; Seder, David B.
Abstract: Aim: Shivering may interfere with targeted temperature management (TTM) after cardiac arrest, contributing to secondary brain injury. Early identification of shivering is challenging with existing tools. We hypothesized that shivering detected by continuous surface sEMG monitoring would be validated with calorimetry and detected earlier than by intermittent clinical observation. Methods: This prospective observational study enrolled a convenience sample of comatose adult cardiac arrest patients treated with TTM at 33 °C. Clinical shivering was monitored hourly using the Bedside Shivering Assessment Scale (BSAS) by bedside nurses who administered intermittent neuromuscular blockade (NMB) when BSAS ≥ 1. The research team monitored independently for shivering with BSAS every 15 min during continuous blinded monitoring of oxygen consumption (VO2 ) via indirect calorimetry and sEMG power during the maintenance phase of TTM. A sustained 20% increase in the 5-min rolling average of VO2 above baseline identified the Gold Standard shivering threshold (VO2 -20). Results: Among 18 patients, clinical shivering was detected 23 times in 14 patients. Hierarchical models to predict a shiver event determined by the VO2 -20 for sEMG power and BSAS revealed an AUC for sEMG power of 0.92 (95%CI = 0.88–0.95), and 0.90 (CI = 0.87–0.94) for BSAS. The optimal threshold of sEMG to predict VO2 -20 was 32 decibels (dB), and this was exceeded 38 (29–56) min before nurse-detected shivering. Conclusions: Shivering was detected by sEMG power earlier than by clinical assessment with BSAS, with similar accuracy compared to the indirect calorimetry gold standard. Continuous sEMG monitoring appears useful for clinical assessment and research for shivering during TTM.